Single-phase single-switch boost PFC regulator with low total harmonic distortion and feedforward input voltage - Athab, H. S. (2008)
The paper proposes a simple harmonic injection technique with feedforward control to modulate the duty cycle of the boost converter's Switch. With this technique a low total harmonic distortion (THD) of the rectifier current can be achieved with a good transient performance which reduces the rectifier's output voltage overshoots during step-up line voltage transients. It is found that third-order harmonic, which is the lowest order harmonic, can be attenuated by adjusting the modulation index (m) of the injected signal. The injected duty cycle variations are naturally synchronized with the input voltage without using an additional harmonic generator and expensive phase-detecting, phase-locking circuits. In addition, to obtain nearly constant harmonic content over a wide range of load variation, a modulation index m is used to update the injected signal with a fraction of the feedback output voltage loop, which reflects the load changes. Simulation and experimental results are presented to con firm the validity of the method.